2021
DOI: 10.3390/catal12010036
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Cobalt Promotion over Ni/CeO2 Catalyst for CO2 Thermal and Plasma Assisted Methanation

Abstract: In recent years, carbon dioxide hydrogenation leading to synthetic fuels and value-added molecules has been proposed as a promising technology for stabilizing anthropogenic greenhouse gas emissions. Methanation or Sabatier are possible reactions to valorize the CO2. In the present work, thermal CO2 methanation and non-thermal plasma (NTP)-assisted CO2 methanation was performed over 15Ni/CeO2 promoted with 1 and 5 wt% of cobalt. The promotion effect of cobalt is proven both for plasma and thermal reaction and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…50 In CO 2 methanation, the bimetallic Ni-Co catalyst supported on ordered mesoporous alumina showed excellent stability at 500 °C for 60 hours, while the Nibased catalyst exhibited a 14.8% decrease in CO 2 conversion. 51 Nevertheless, the favorable impact of bimetallic Ni-Co catalysts, as reported in certain studies, 51,52 did not manifest evidently in other investigations 53,54 since large metal particles were formed using Co/Ni/Al 2 O 3 and resulted in lower CH 4 yield, in addition to CO formation. 53 Hasrack et al 54 showed comparable stability at 250 °C for 5 hours, with a slightly higher performance of 1Co15Ni/CeO 2 catalyst.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 86%
“…50 In CO 2 methanation, the bimetallic Ni-Co catalyst supported on ordered mesoporous alumina showed excellent stability at 500 °C for 60 hours, while the Nibased catalyst exhibited a 14.8% decrease in CO 2 conversion. 51 Nevertheless, the favorable impact of bimetallic Ni-Co catalysts, as reported in certain studies, 51,52 did not manifest evidently in other investigations 53,54 since large metal particles were formed using Co/Ni/Al 2 O 3 and resulted in lower CH 4 yield, in addition to CO formation. 53 Hasrack et al 54 showed comparable stability at 250 °C for 5 hours, with a slightly higher performance of 1Co15Ni/CeO 2 catalyst.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 86%
“…In situ DRIFTS and temperature-programmed surface reaction (TPSR) results indicated that the incorporation of Co accelerated the conversion of intermediates and decreased the activation temperature of CO 2 , due to the synergistic effect of Ni and Co on the 12Ni3Co/M–Ce80Zr20 catalyst. Recently, Hasrack et al 145 found that CO 2 methanation performance could be improved over 15Ni/CeO 2 catalysts via adding 1 and 5 wt% of Co. On the basis of activity evaluation and CO 2 -TPD results, the relationship between catalytic activity and the number of medium basic sites could be well established. Although the addition of Co decreased the total basicity, the amount of medium basic sites greatly increased, which was widely considered a key factor in the methanation reaction.…”
Section: Strategies To Raise the Catalytic Performance Over Ceria-bas...mentioning
confidence: 99%
“…In effect, the reducibility of Ni species was modified, with Mn species facilitating the reduction of nickel, as opposed to the indium-containing catalyst. Furthermore, adding cobalt in Ni/CeO 2 catalysts significantly enhanced CO 2 conversion and methane selectivity, with the CoNi/CeO 2 catalyst exhibiting the highest amount of medium basic sites and the optimum performance in both plasma and non-plasma reactions [266]. In this regard, europium ions (Eu 3+ ) were introduced into a nickel-ceria catalyst with the scope of the enhancement of metal-support interactions.…”
Section: Ceo 2 -Based Catalysts For the Sabatier Reactionmentioning
confidence: 99%